Characterization of calcium alginate beads of 5-fluorouracil for colon delivery - Patel, Hetal K; Nagle, Amrita; Murthy, R S R (Asian Journal of Pharmaceutics (AJP), 2014)
Amultiparticulate system combining pH-sensitive property and specific biodegradability for colon targeted delivery of 5-fluorouracil (5-FU) was examined. The purpose of this study was to prepare and evaluate the colon-specific alginate beads of 5-FU for the treatment of colon cancer. Calcium alginate beads were prepared by extruding 5-FU loaded alginate solution to calcium chloride solution, and gelled spheres were formed instantaneously by ionotropic gelation reaction using different ratios of FU and alginate, alginate and calcium chloride, stirring speeds (500-1500 rpm), and reaction time. The core beads were coated with Eudragit S-100 to prevent drug release in the stomach and provide controlled dissolution of enteric coat in the small intestine and maximum drug release in the colon. Morphology and surface characteristics of the formulation were determined by scanning electron microscopy. In vitro drug release studies were performed in conditions simulating stomach to colon transit. No significant release was observed at acidic pH, however, when it reached the pH where Eudragit S-100 starts to dissolve, drug release was observed. Also, release of drug was found to be higher in presence of rat caecal content.